Mg2−xMnxSiO4 compound obtained via sol–gel method: structural, morphological and electrochemical properties - Tamin, S.H.; Dzulkurnain, Nurul Akmaliah; Adnan, Syed Bahari Ramadzan Syed; Jaafar, Mohd Hilmi; Mohamed, Nor Sabirin (Springer Verlag, 2018)
Prospective cathode materials Mg2-xMnxSiO4 (0.0 ≤ x ≤ 0.4) for magnesium-ion secondary battery were synthesized using sol gel method. Crystalline structure, morphology, particle size, electrical and electrochemical properties of the samples were investigated. X-ray diffraction patterns of the materials exhibited no extra peak for x ≤ 0.6 indicated that Mg2-xMnxSiO4 materials were successfully synthesized. Mn doping in magnesium site did not affect the formation of single phase, and this probably due to the low concentration of Mn to induces structural changes. Mn doping contributed to the enhancement of the electrochemical performance of Mg2SiO4. For this work, Mg1.4Mn0.6SiO4 which possesses the largest unit cell volume, smallest charge transfer resistance, and highest conductivity value showed the most promising electrochemical performance compared to the other samples. These results indicated the suitability of the Mg2-xMnxSiO4 to be exploiting further for potential applications as solid electrolytes in electrochemical devices and strengthen the fact that doping could be an effective way to enhanched the structural, electrical and electrochemical performance of materials.